Brivaracetam for the treatment of epilepsy. (22nd January 2016) - Klein, Pavel; Tyrlikova, Ivana; Brazdil, Milan; Rektor, Ivan
ABSTRACT: Introduction: Approximately one third of patients with epilepsy fail to respond to existing medications. Levetiracetam is an effective antiepileptic drug (AED) postulated to act by binding to synaptic vesicle protein 2A. Brivaracetam is a novel high affinity SV2A ligand with approximately 20-fold higher affinity for SV2A protein than levetiracetam. It is at an advanced stage of clinical development for treatment of epilepsy. Areas covered: This article reviews animal data, pharmacokinetics, and phase 1-3 data of Brivaracetam treatment of epilepsy. Brivaracetam has broad-spectrum anticonvulsant activity in animal models. Expert Opinion: Phase 1 studies indicated that single oral doses of 5-800 mg and repeated oral doses of up to 600 mg were well tolerated and showed favorable pharmacokinetic profile. Phase 2 studies indicated good safety and tolerability of brivaracetam in the dose range of 5-150 mg/day and provided proof of concept for efficacy in treating refractory partial onset seizures. Efficacy and safety have been evaluated in 4 phase 3 studies with dose range of 5-200 mg which have demonstrated efficacy in the range of 100-200 mg/day dose and, in most studies, also with 50 mg/day dose, and good safety and tolerability profile across 5-200 mg doses in adjunctive treatment of refractory partial onset seizures.